Protein and lysine requirements for maintenance and for tissue accretion in Atlantic salmon (Salmo salar ) fry. - ABBOUDI, T.; Mambrini, Muriel; OOGHE, W.; Larondelle, Yvan; Rollin, Xavier (HAL CCSD, 2006)
International audience